Reversal of Rocuronium Induced Neuromuscular Blockade in Lung Resection Surgery: A Comparison of Sugammadex and Neostigmine - (:unkn) unknown (My University, 2019)
Introduction: The aim of this study was to compare sugammadex and neostigmine in terms ofreversing time, recovery time and extubation time in reversal of rocuronium-inducedneuromuscular block in patients undergoing lung resection surgery.Method: A total of 60 patients under 75 years of age with an ASA status of II-III undergoing electivepulmonary resection (lobectomy, pneumectomy, wedge resection) who had adequate left ventriclefunction (EF >40%), normal renal, hepatic, and mental functions, were included in this study Patientswere assigned into neostigmine (Group N, n=30) and sugammadex (Grup S, n=30) groups.Results: Time from starting of neuromuscular blockade reversing agent till reaching TOF>0.9 wassignificantly shorter in Group S (p=0.001). Similarly, extubation time and recovery time weresignificantly shorter in Group S (p=0.05; p=0.012, respectively). No statistically significantdifferences were observed between the two groups in terms of the operation time and durationof ICU stay. Postoperative complications were similar in both groups. Postoperative residualcurarisation was not observed in both groups.Conclusion: In lung resection surgery, sugammadex appears to be a superior selective relaxantbinding agent as compared to neostigmine in the reversal of rocuronium- induced neuromuscularblock with earlier recovery and earlier achievement of TOF ratio of 0.9.

Amaç: Bu çalışmanın amacı, tek akciğer ventilasyonu ile opere edilen hastalarda, rokuronyum ile oluşturulan nöromüsküler blokajın geri döndürülmesinde sugammadeks ve neostigminin geri döndürme süresi, derlenme süresi, ekstubasyon süresi açısından karşılaştırılmasıdır. Yöntem: Çalışmaya elektif lobektomi, pnömektomi veya wedge rezeksiyon planlanan ASA 2-3 grubu, 75 yaş altı, renal ve hepatik fonksiyon bozukluğu olmayan ve sol ventrikül ejeksiyon fraksiyonu %40’ın üzerinde olan toplam 60 hasta dâhil edildi. Hastalar Grup N (Neostigmine Grubu) ve Grup S (Sugammadeks Grubu) olmak üzere 2 gruba ayrıldı. Bulgular: Nöromüsküler blokajı geri döndürmek için uygulanan ajan sonrası TOF>0.9’a ulaşana kadar geçen süre Grup S’de anlamlı olarak daha kısa bulundu (p=0.001). Benzer şekilde ekstübasyon süresi ve derlenme süresi Grup S’de anlamlı olarak daha kısaydı (sırasıyla p=0.05; p=0.012). Ameliyat süreleri ve yoğun bakımda kalış süreleri açısından 2 grup arasında istatistiksel olarak anlamlı bir farklılık gözlenmedi. Postoperatif komplikasyonlar açısından her 2 grup arasında anlamlı farklılık bulunamadı. Hiçbir hastada postoperatif rekürarizasyon gözlenmedi. Sonuç: Çalışmamız, elektif akciğer rezeksiyonu ameliyatlarında nöromusküler bloke edici ajanın etkilerinin geri döndürülmesinde sugammadeksin neostigmine göre TOF oranının 0.9’a daha erken ulaşmasını sağlaması ve daha erken derlenmeye neden olması açısından daha üstün olduğunu göstermektedir.
Akciğer Rezeksiyonu Cerrahisinde Rokuronyumun Nöromüsküler Blok Etkisinin Geri Döndürülmesi: Sugammadeks ve Neostigminin Karşılaştırılması
Keywords: Cerrahi